Grafting of Gold Nanoparticles on Glass Using Sputtered Gold Interlayers - Ondřej Kvítek; Robin Hendrych; Zdeňka Kolská; Václav Švorčík (Journal of Chemistry)
Three-step preparation of nanostructured Au layer on glass substrate is described. The procedure starts with sputtered gold interlayer, followed by grafting with dithiols and final coverage with gold nanoparticles (AuNPs). Successful binding of dithiols on the sputtered Au film was confirmed by X-ray photoelectron spectroscopy measurement. AuNPs bound to the surface were observed using atomic force microscopy. Both single nanoparticles and their aggregates were observed. UV-Vis spectra show broadening of surface plasmon resonance peak after AuNPs binding caused by aggregation of AuNPs on the sample surface. Zeta potential measurements suggest that a large part of the dithiol molecules are preferentially bound to the gold interlayer via both –SH groups.